ANALISA PROTEKSI HILANG EKSITASI PADA GENERATOR SINKRON DI PLTGU MUARA TAWAR GT UNIT 1.3 - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
One of the operating disruptions that occur in the synchronous generator is the loss of excitation. Where this interference will cause the generated reactive power generator is reduced even lost so that the synchronous generator must absorb the reactive power of the system. If this condition occurs continuously can cause damage to the stator coil, will occur worsening insulation and the stator end iron so as to cause short circuit, or interruption of soil relations in the future. So to anticipate the impact of such disturbances required a protection system. The protection system used in PLTGU Muara Tawar GT unit 1.3 is a minimum reactance relay. This jurnal discusses how to determine the value of loss excitation protection setting using minimum reactance relay and offset relay mho so that synchronous generator can work optimally. From the research calculation the minimum reactance relay usage will work on XA-setting value zone (-2.55 p.u) with 0.5 seconds delay time, XB-setting (offset) of -0.1156 p.u with 0.5 seconds delay time. As for offset relay mho will work on zone 1 and zone 2 for offset value of -0.109 p.u with delay time 0.1 second. As for zone 1 for the base impedance ( ) of -1.0 p.u with a delay time of 0.1 seconds and zone 2 synchronous reactance value ( of 2.423 p.u with a delay time of 0.5 seconds. From those results it is considered sufficient to detect the loss of excitation in the synchronous generator.